Temperature and photoperiod differentially impact maternal phenotypes in diapause egg-laying Aedes albopictus mosquitoes. - In Hae Lee; Anthony S Lee; Helen V Kogan; Linhan Dong; Laura B Duvall (Public Library of Science (PLoS), 2024)
Background Aedes albopictus (Skuse 1894) mosquitoes can transmit deadly arboviruses and are globally invasive due to their ability to survive in both tropical and temperate climates. Although adults cannot survive harsh winters, females are capable of anticipating seasonal change and producing overwintering diapause (DP) eggs that remain in a state of arrested development over the winter and hatch when favorable conditions return in the spring. While low temperatures can facilitate DP entry under short photoperiods, temperature signals alone are not sufficient to induce DP. Methodology/principal findings To identify maternal phenotypes predictive of DP egg production in laboratory conditions, we characterized aspects of maternal physiology and behavior to identify those that correlate with DP egg production and changes in photoperiod, versus changes in temperature. Neither changes in temperature nor photoperiod impacted protein preference, blood meal consumption, or total number of eggs produced per female. Egg retention and oviposition timing were influenced by temperature, independent of DP egg production. However, females housed under short photoperiod conditions showed increased starvation resistance, despite showing similar levels of locomotor activity and internal stores of triacylglycerols, glucose, glycogen, and trehalose compared to females housed in long photoperiods. Conclusions/significance These results suggest that temperature and photoperiod differentially affect maternal phenotypes and identify starvation resistance as a maternal phenotype that is influenced by photoperiod and correlates with DP egg status.